2010
DOI: 10.1177/1365480210385668
|View full text |Cite
|
Sign up to set email alerts
|

The theory into practice dilemma: Lesson planning challenges facing Botswana student-teachers

Abstract: The aim of this study is to examine the problems facing University of Botswana's PostGraduate Diploma in Education (PGDE) student-teachers with respect to their pedagogical practices during school placements. The study attempts to locate the issue of lesson plans and use of behavioural objectives within the general discourse on school improvement. It highlights the strengths and weaknesses of behavioural objectives, particularly the focus on the input-output process model of teaching and learning. Methods used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…In addition, according to Boikhutso (2010), different formula is in fact more likely to pose a dilemma and uncertainty about how student-teachers plan and implement the daily pedagogical routine of the teaching-learning process. However, he added that it does not matter if every school has its own manual in creating lesson plan, as long as the teachers understand the most important attributes of lesson plans and planning is that they add value to teaching and classroom instruction (Boikhutso, 2010).…”
Section: Challenges In Dealing With Different Formula Lesson Planmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, according to Boikhutso (2010), different formula is in fact more likely to pose a dilemma and uncertainty about how student-teachers plan and implement the daily pedagogical routine of the teaching-learning process. However, he added that it does not matter if every school has its own manual in creating lesson plan, as long as the teachers understand the most important attributes of lesson plans and planning is that they add value to teaching and classroom instruction (Boikhutso, 2010).…”
Section: Challenges In Dealing With Different Formula Lesson Planmentioning
confidence: 99%
“…In addition, according to Boikhutso (2010), different formula is in fact more likely to pose a dilemma and uncertainty about how student-teachers plan and implement the daily pedagogical routine of the teaching-learning process. However, he added that it does not matter if every school has its own manual in creating lesson plan, as long as the teachers understand the most important attributes of lesson plans and planning is that they add value to teaching and classroom instruction (Boikhutso, 2010). The important point in lesson planning is having clear understanding of overall objectives which help teachers concentrate on a stable set of tasks they design, thus reducing the amount of time needed to generate new ideas for the next day's class (Snow & Campbell, 2006), no matter how the formula is.…”
Section: Challenges In Dealing With Different Formula Lesson Planmentioning
confidence: 99%
“…Boikhutso (2010) conducted research about "lesson planning challenges facing Botswana student-teachers". The results revealed that student-teachers are more predisposed to rely on the use of knowledge and comprehension type of behavioral verbs in their lesson plans.…”
Section: Related Research Reportmentioning
confidence: 99%
“…Lesson planning is an essential aspect of teaching that needs to be prepared before the lesson to help teachers deliver the subject's material more effectively, efficiently, and organized-designing the lesson plan before the teaching and learning process can help teachers to visualize their learning process in the classroom (Haynes, 2010). Besides, designing the lesson plan and preparing the lesson before teaching is considered more effective for teaching and learning (Boikhutso, 2010). İn conclusion, a lesson plan is teachers' effort for designing guidelines for an effective, efficient, and organized learning process.…”
Section: Introductionmentioning
confidence: 99%